2021
DOI: 10.3390/foods10102381
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol-Induced Hepatotoxicity and Alcohol Metabolism Regulation by GABA-Enriched Fermented Smilax china Root Extract in Rats

Abstract: Chronic alcohol consumption can cause hepatic injury and alcohol-induced toxicities. Extracts from Smilax china root have been widely used in traditional medicine and for their potential pharmacological benefits. We aimed to determine if fermented Smilax china extract (FSC) regulates alcoholic fatty liver and liver injury using two in vivo experiments. Sprague-Dawley rats were administered ethanol (3 g/kg b.w.; po) with or without FSC pretreatment to induce an acute hangover. In another experiment, rats were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 34 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…The liver is an organ with mainly metabolic functions and has functions such as de‐oxidation, storage of liver sugar, and secretory protein synthesis (Boby et al, 2021 ). Figure 3A shows the liver tissue anatomy of each group.…”
Section: Resultsmentioning
confidence: 99%
“…The liver is an organ with mainly metabolic functions and has functions such as de‐oxidation, storage of liver sugar, and secretory protein synthesis (Boby et al, 2021 ). Figure 3A shows the liver tissue anatomy of each group.…”
Section: Resultsmentioning
confidence: 99%
“…When there is an excessive of ROS production, an increase serum levels of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) will eventually occur [ 96 , 97 ]. A long-term consumption of alcohol may lead to hepatoxicity [ 98 ]. Moreover, certain medications, e.g., paracetamol, sodium diclofenac, diethyldithiocarbamate, ketoconazole, and anti-tuberculosis, may also initiate liver damage [ 94 , [99] , [100] , [101] ].…”
Section: Discussionmentioning
confidence: 99%
“…Animal experiments have demonstrated that the GABA-rich Smilax extract (FSC) improves alcohol metabolism and reduces alcohol-induced liver damage. FSC improved hangovers by stimulating hepatic alcohol metabolism, commercially acclaimed for its anti-alcoholism effects [ 55 ]. In traditional Chinese medicine, P. lobata flowers ( Puerariae Flos ) have been used primarily to relive alcohol related problems and injury of liver [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%